Inclusive Subtitles for All: Developing Practices and Guidelines for Accessible Media Content in Newly Experimenting Territories (London Journal of Research In Humanities and Social Sciences, 2024)
This article provides a descriptive and analytical overview of the ongoing practical projects and action research intended to implement inclusive practices in the media sector in Malta. It also provides a transversal analysis of the findings across a series of applied and experimental studies investigating the practice of inclusive subtitles, a translation mode that targets a wide spectrum of viewers providing linguistic, cultural, and sensory access. The studies carried out adopt a user-centred approach and aim to identify the needs of the local audience while testing and shaping a set of proposed guidelines to be adopted by local practitioners and stakeholders. The main findings and insights are based on the observation of patterns and potential norms that emerged across the studies and corroborate, or otherwise, the specifications and recommendations in the said guidelines, while identifying the need for further research focusing on specific aspects. This paper could provide a model for similar territories that are seeking to engage in inclusive practices applied to media content.
Keywords: Social rapports; deflation and inflation; constant & coordinated development; Adolescence; Developmental Task; Identity; Parenting function; Parentification.; Literature-in-English; Debasish Lahiri; Concept Poetry; Postcolonial Intersectionalities; accessibility; inclusivity; audiovisual translation; inclusive subtitles; universalist approach